THE RELATIONSHIP BETWEEN SHARED LEADERSHIP AND TEAM PERFORMANCE - Tina Melinda; Natalia Christiani; Imelda Ritunga; Tony Antonio; Teofilus Teofilus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
A leader is a person who will lead an organization to achieve goals, by motivating its members to achieve good performance. Shared leadership is one of the leadership styles that can be used to achieve good performance, because shared leadership is to provide opportunities for its members to contribute to performance achievement. This study aims to determine the relationship between shared leadership which has two dimensions, namely Task Oriented Shared Leadership (TOSL) and Relation Oreinted Shared Leadership (ROSL) to team performance. The sample used in this study was 216 people from three universities in the cities of Surabaya, Manado and Jakarta. The result is that there is a relationship between shared leadership and team performance. High TOSL and ROSL will result in high team performance or vice versa.